The phenomenon of magnetic exchange bias in ferromagnetic nanocomposites grown by electron beam evaporation - Radchenko, M.V.; Lashkarev, G.V.; Bugaiova, M.E.; Baibara, O.E.; Knoff, W.; Story, T.; Krushinskaya, L.A.; Stelmakh, Y.A.; Dumond, Y. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
For the first time, in ferromagnetic nanocomposites Co/СoO/Al₂O₃ formed by two-crucible electron beam evaporation with deposition on a polycor substrate, the magnetic exchange bias was observed. It is associated with the magnetic interaction of the ferromagnetic metal core of Co nanoparticles with the antiferromagnetic CoO layer on their surface. The low value of magnetic exchange bias is attributed to the small thickness of the CoO shell, inasmuch as the energy of exchange magnetic anisotropy, which decreases with diminishing the antiferromagnetic CoO layer thickness, cannot provide a significant increase of the coercive force when changing the magnetic field direction. The ferromagnetic nanocomposites with the magnetic exchange bias can be used as a bias magnetic layer for magnetoresistive sensors.